How team leaders can improve virtual team collaboration through trust and ICT: A conceptual model proposition - Kauffmann, David (Economics and Business Review, 2015)
The purpose of this paper is to present a conceptual model to facilitate thedevelopment of collaboration within virtual teams. The model claims that a high levelof communication through ICT is an important antecedent for collaboration mediatedby the level of trust among the team. Furthermore and according to the model,Team Leaders can have a major impact on the communication effectiveness and onthe level of team trust.